Development and Validation of a Novel ELISA for the Detection of Neospora Caninum Antibodies in Bovine Sera - Mansilla, Florencia Celeste (2020)
Neospora caninum is a world-wide distributed apicomplexan parasite, causative agent of bovine neosporosis, which is one of themajor causes of reproductive losses in cattle affecting both dairy and beef industries. Several techniques are regularly used for the diagnosis of bovine neosporosis. Amongst them, serological techniques are generally preferred, being IFAT the traditionally accepted reference method for diagnosis (gold standard). However, ELISA has become the most eligible method for large-scale screening ofspecific antibodies against N. caninum in diagnostic laboratories around the world, providing results that can be easily standardized between laboratories, within a few hours at a relative low-cost. There is no local production of commercial ELISA tests nor in Argentina neither in South America, therefore they must be purchased abroad, turning unfeasible the routinely use of ELISA tests. Here we have developed and validated accordingly to OIE specifications a novel ELISA test based on soluble antigens from N. caninum tachyzoites to accurately determine the presence of specific antibodies anti- N. caninum antigens in bovine sera samples, enabling the rapid, objective and low-cost diagnosis of bovine neosporosis in Argentina; replacing IFAT and avoiding delays and high importation taxes.